2009
DOI: 10.1159/000262286
|View full text |Cite
|
Sign up to set email alerts
|

Age-Related Changes in Neuromuscular Function and Performance following a High-Intensity Intermittent Task in Endurance-Trained Men

Abstract: Background: Much attention has been focused on the need to design strategies to increase functional capacities in older populations. This has raised several questions regarding the ability of regular endurance training to preserve functional capacity with age. Objective: The purpose of this study was to examine the age-associated changes in neuromuscular function in endurance-trained men before and after a high-intensity, intermittent fatiguing task. Method: Twenty-six healthy endurance-trained male subjects: … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
14
0
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 21 publications
(17 citation statements)
references
References 84 publications
2
14
0
1
Order By: Relevance
“…A useful method for assessing the effects of age on physiological functional capacity is to determine decrements in exercise performance with aging, in elite athletes 10. Studying elite athletes rather than sedentary subjects allows for a model relatively free of confounding factors, such as variations in physical ability and disease 6,14,15…”
Section: Discussionmentioning
confidence: 99%
“…A useful method for assessing the effects of age on physiological functional capacity is to determine decrements in exercise performance with aging, in elite athletes 10. Studying elite athletes rather than sedentary subjects allows for a model relatively free of confounding factors, such as variations in physical ability and disease 6,14,15…”
Section: Discussionmentioning
confidence: 99%
“…Observing master athletes can give insight into ageinduced changes in physiology and adaptability, thus enabling scientists to develop more concise and effective recuperation and mobilization programs. Recent studies have shown that master endurance athletes are able to maintain their performance despite exhibiting the structural changes in muscle performance and in maximal aerobic power which are classically associated with aging Tanaka and Seals 2008;Bieuzen et al 2010;Louis et al 2009). …”
Section: Introductionmentioning
confidence: 99%
“…Previous research has suggested that athletes who maintain a high level of training volume and intensity into older age are able to significantly attenuate age-related decrements in endurance performance (Berger et al, 2006;Bieuzen et al, 2010;Darr et al, 1988;Ransdell et al, 2009;Sultana et al, 2012). The ability to maintain performance through systematic training was also highlighted in a recent investigation by Gent and Norton (2013) who measured anaerobic and aerobic capacities using cycle ergometry in 173 healthy masters cyclists and triathletes aged between 35-64 years.…”
Section: Masters Athletesmentioning
confidence: 97%
“…Recent research comparing younger and masters athletes has increased knowledge in this specific population and shown the significance of neuromuscular recovery in masters athletes. Despite this, limited research has empirically examined recovery kinetics of older versus younger athletes (Bieuzen, Hausswirth, Louis, & Brisswalter, 2010;Darr et al, 1988;Easthope et al, 2010;Fell, Haseler, Gaffney, Reaburn, & Harrison, 2006;Fell, Reaburn, & Harrison, 2008). Moreover, the possible mechanisms explaining thee slower recovery kinetics in older athletes remain to be investigated.…”
mentioning
confidence: 99%